2002
DOI: 10.1206/0003-0082(2002)374<0001:paombn>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Morpho Butterflies (Nymphalidae, Morphinae): Implications for Classification and Natural History

Abstract: The classification of butterflies in the widely recognized genus Morpho previously used subgenera that were assumed to constitute natural species groups. Cladistic analysis of 120 characters provided a well-resolved tree showing that some subgenera do not constitute monophyletic groups. This study supported some traditional taxonomic species groupings, but rejected the concept of subgenera for Morpho. Therefore, we formally redefined the genus to be consonant with the assumptions of phylogenetic classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
55
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(62 citation statements)
references
References 22 publications
(6 reference statements)
7
55
0
Order By: Relevance
“…Eleven gains and four losses of the polarized pattern occurred in the butterflies examined, according to the most recently available published phylogenies. (Brower, 1994;Brower and Egan, 1997;Penz, 1999;Wahlberg and Zimmermann, 2000;Willmott et al, 2001;Wahlberg, 2001;Penz and DeVries, 2002;Blum et al, 2003;Wahlberg et al, 2003;Frietas and Brown, Jr, 2004;Murray and Prowell, 2005 Ten gains and three losses were located on the nymphalid clade; of these, nine gains and three losses were located on branches designated as forest dwelling species. Those butterflies that exhibited polarized reflectance patterns were significantly more likely to exist within a forest light habitat (PϷ0.008).…”
Section: Concentrated Changes Testmentioning
confidence: 99%
“…Eleven gains and four losses of the polarized pattern occurred in the butterflies examined, according to the most recently available published phylogenies. (Brower, 1994;Brower and Egan, 1997;Penz, 1999;Wahlberg and Zimmermann, 2000;Willmott et al, 2001;Wahlberg, 2001;Penz and DeVries, 2002;Blum et al, 2003;Wahlberg et al, 2003;Frietas and Brown, Jr, 2004;Murray and Prowell, 2005 Ten gains and three losses were located on the nymphalid clade; of these, nine gains and three losses were located on branches designated as forest dwelling species. Those butterflies that exhibited polarized reflectance patterns were significantly more likely to exist within a forest light habitat (PϷ0.008).…”
Section: Concentrated Changes Testmentioning
confidence: 99%
“…Considerable insight into the evolution of Morpho has been gained by phylogenetic studies (Penz and DeVries, 2002;Penz et al, 2012;Cassildé et al, 2012;Blandin and Purser, 2013). Furthermore, detailed anatomical and optical investigations of the scales that cover the wings have yielded substantial knowledge of the physical basis of the brilliant-blue colored wings (Ghiradella, 1984;Vukusic et al, 1999;Yoshioka and Kinoshita, 2004;Berthier, 2007;Kinoshita, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Th e morphological results supported the monophyly of eight subgenera, and the subgenus Cytheritis Le Moult & Réal 1962, was divided into two clades. Th us, the phylogenies of Penz & DeVries (2002) and , despite of some convergences, diff ered strongly.…”
mentioning
confidence: 99%
“…Up-to-date distribution maps were provided for all species and subspecies by Blandin (2007a). Interestingly, Morpho species can be separated into strongly diff erentiated groups, considered by authors as subgenera (Le Moult & Réal 1962, 1963Blandin 2007a), or even as genera (Bilotta 1992(Bilotta , 1994a(Bilotta , 1994b (Penz & DeVries 2002). As three subgenera did not appear monophyletic units in their phylogeny, these authors concluded that the subgeneric classifi cation of the genus should be abandoned.…”
mentioning
confidence: 99%